CREATING DIGITAL TEACHING MATERIALS THAT UTILIZE AUGMENTED REALITY HAS THE POTENTIAL TO ENHANCE STUDENT'S CRITICAL THINKING ABILITIES - Firdaus, Fikri Zauharul; Khodijah, Neneng Fauziah; Inayah, Ina Nurul (PD PGMI se Indonesia, 2024)
This study aims to create digital educational resources centered around Augmented Reality (AR) that focus on plants' various parts and functions, with the intention of enhancing critical thinking abilities. The study follows a development research approach, utilizing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) research design. Data was gathered through expert evaluations, teacher assessments, test questions, student worksheets, and student response questionnaires. The data was then quantitatively analyzed descriptively. The findings revealed that the teaching materials received high ratings from experts, with a score of 96% and a CVR and CVI of 0.95. Before using the teaching materials, students' critical thinking skills were measured at 62.55, significantly improving to 87.55 after implementing the materials. The increase in students' critical thinking skills was measured at 65.55. Additionally, 91% of students strongly agreed with the effectiveness of the Augmented Reality (AR)-based digital teaching materials. This research encourages technology developers to create more AR-based educational content that suits the needs of the curriculum and the target skills they want to improve, such as critical thinking.